(untitled) (ENTHYMEMA, 2011)
In this article we will analyse the use of the enjambment in the collection of poems by Giovanni Giudici La vita in versi. In particular, we will consider its metric-rhythmic consequences and its intensity and we will analyse its stylistic-expressive implications. This will lead us to verify the interaction of the metric-semantic level and of the poetic signifier in producing the effectiveness and the memorability of the collection, which is one of the most important products of the poetic realism in the Italian Twentieth Cetury.